The 2018 Conference on Artificial Life 2018
DOI: 10.1162/isal_a_00113
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Optimization with Composite Objectives and Novelty Selection

Abstract: An important benefit of multi-objective search is that it maintains a diverse population of candidates, which helps in deceptive problems in particular. Not all diversity is useful, however: candidates that optimize only one objective while ignoring others are rarely helpful. This paper proposes a solution: The original objectives are replaced by their linear combinations, thus focusing the search on the most useful tradeoffs between objectives. To compensate for the loss of diversity, this transformation is a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Previous work in the sorting networks domain demonstrated that composite novelty can match the minimal known networks up to 18 input line with reasonable computational resources [39,40]. The goal of the sorting network experiments was to achieve the same result faster, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work in the sorting networks domain demonstrated that composite novelty can match the minimal known networks up to 18 input line with reasonable computational resources [39,40]. The goal of the sorting network experiments was to achieve the same result faster, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative method is to use composite multi-objective axes to focus the search on the area with most useful tradeoffs [39]. Since the axes are not orthogonal, solutions that optimize only one objective will not be on the Pareto front.…”
Section: Multi-objective Optimizationmentioning
confidence: 99%
See 3 more Smart Citations